(untitled) (Homoeopathy for All, 2022)
Biochemic combinationsor cell salts or tissue salts have been dispensed as combination since the time of Schussler. A German physician Dr. Schussler realized that a deficiency of certain tissue salts can lead to a number of diseases. These salts are normal components of healthy tissues are essential for the growth and development of the body. Although this system is considered to be an offshoot of Homoeopathy, it has its independent standing. Unlike homeopathic medicines that are in thousands and are available in various potencies or scales, the biochemic remedies are just twelve in number and are available in the 3X, 6X, 12X,